1995
DOI: 10.1182/blood.v85.4.1122.bloodjournal8541122
|View full text |Cite
|
Sign up to set email alerts
|

Development of a marrow transplant regimen for acute leukemia using targeted hematopoietic irradiation delivered by 131I-labeled anti-CD45 antibody, combined with cyclophosphamide and total body irradiation

Abstract: In an attempt to decrease the relapse rate after bone marrow transplantation (BMT) for advanced acute leukemia, we initiated studies using 131I-labeled anti-CD45 antibody (BC8) to deliver radiation specifically to hematopoietic tissues, followed by a standard transplant preparative regimen. Biodistribution studies were performed in 23 patients using 0.5 mg/kg trace 131I-labeled BC8 antibody. The BC8 antibody was cleared rapidly from plasma with an initial disappearance half-time of 1.5 +/- 0.2 hours, presumabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(30 citation statements)
references
References 22 publications
0
24
0
6
Order By: Relevance
“…The following limiting organ doses were defined: BM 35 Gy, kidney 12 Gy and liver 20 Gy. These doses were based on the experience of Matthews et al (1996) and published studies on the radiation tolerance of organs (Emami et al, 1991;Matthews et al, 1996). The therapeutic antibody was given intravenously in 1 (yttrium) or 2 (rhenium) fractions over a period of 10 min on day )14 relative to the scheduled transplantation date in order to guarantee the elimination of the nuclide.…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…The following limiting organ doses were defined: BM 35 Gy, kidney 12 Gy and liver 20 Gy. These doses were based on the experience of Matthews et al (1996) and published studies on the radiation tolerance of organs (Emami et al, 1991;Matthews et al, 1996). The therapeutic antibody was given intravenously in 1 (yttrium) or 2 (rhenium) fractions over a period of 10 min on day )14 relative to the scheduled transplantation date in order to guarantee the elimination of the nuclide.…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…Hence, the outlook for patients with therapy‐related AML remains poor even after allogeneic transplantation. One promising alternative strategy approach is to add monoclonal antibodies targeted to host haematopoietic cells in the conditioning regimen as a means of eradicating residual leukaemia ( Matthews et al , 1995 ). Another is to enhance the immune‐mediated graft vs. leukaemia effect by infusing donor lymphocytes after subablative therapy ( Giralt et al , 1997 ).…”
Section: Remission Retrieval Therapy and Outcomementioning
confidence: 99%
“…Targeted radiotherapy is one potential option to overcome this paradigm. Clinical studies have shown that monoclonal antibodies (mAb) labelled with radioactive isotopes successfully deliver higher radiation doses to the bone marrow and the spleen (Matthews et al, 1995;Bunjes et al, 2001;Pagel et al, 2006). A recent study (Ringhoffer et al, 2005) has already demonstrated the principal feasibility of the combination of radioimmunotherapy and reduced-intensity conditioning.…”
mentioning
confidence: 99%